Norge og EU : partnere i Arktis - Wegge, Njord (University of Tromsø, 2012)
This article raises three main questions: (i) What characterizes the EEC/EU's relationship to the Arctic? (ii) What issues/areas have caused problems for the EU in becoming a more relevant actor in the Arctic? (iii) To what degree has Norway been able to exert influence on the Union's ongoing Arctic policy development? By chronologically reviewing the EEC/EU's relationship to the Arctic the article demonstrates that the intensity and interest for the Northern region has varied dramatically from great interest to near ignorance. While the Greenlandic population in 1982, due to cultural and economic disputes, left the EEC, the Union's most recent challenges with respect to becoming a relevant actor in the Arctic has concerned disagreements with some of the Arctic states. These disputes have primarily included discord on 1. The Law of the seas' role in the Arctic, 2. the EU's desire to become a permanent observer in the Arctic Council and finally, 3. The EU's ban on seal products in the Common market. The article concludes by describing how Norway has been one, if not the most, important Arctic state for the Union, and that Norway has benefitted from a cooperative approach towards the EU. The cooperative approach has indirectly given Norway an opportunity to influence the outcome of the EU's Arctic policy.